Heritability and public policy reconsidered, again - Cornelius A. Rietveld (Tinbergen Institute, 2024)
I offer a way out of the Taubman-Goldberger controversy on the public policy (ir)relevance of heritability studies by arguing for a quasi-experimentally controlled comparison of the estimates that these studies provide. If the environments individuals are exposed to are under such control, changes in the genetic and the common environment (family) variance components underlying inter-individual differences can be ex-post informative regarding the evolvement of sources of inequalities in a population. Using administrative data from the Netherlands, I empirically illustrate this reappraisal of heritability studies by estimating two different gene-environment interactions in test scores from a highstakes national educational achievement test
Keywords: I24; I38; J18; 330; Education; Equality of opportunity; Inequality; Heritability; Public policy